The Status And Code Of Ethics Of Early Childhood Education Teachers In Enhancing Educational Professionalism In Indonesia - Aulia, Tri Imanda; Oktavia , Mela; Rahma , Aisyah Nur; Mayasari , Henni (Jurnal Pendidikan Rafflesia, 2025)
The Early Childhood Education (PAUD) teaching profession holds a strategic role in national education development, serving as learning facilitators, character mentors, and moral exemplars for young children. However, in practice, the professional status of PAUD teachers in Indonesia still faces various challenges, including formal recognition, welfare, and the implementation of the professional code of ethics in daily learning activities. This study critically examines the professional status of PAUD teachers and the implementation of the Indonesian Teacher Code of Ethics within the context of early childhood educational professionalism. The study employs a descriptive qualitative approach through literature analysis and relevant regulatory documents, such as Law No. 14 of 2005 on Teachers and Lecturers, and the Indonesian Teacher Code of Ethics (PGRI, 2013). The findings indicate that, although PAUD teachers are formally recognized as professionals with competency standards and certification, gaps remain between normative ideals and ethical practice in the field. Factors such as low ethical literacy, weak supervision, disparities in welfare, and limited social recognition of PAUD teachers constitute major barriers to improving professionalism. The article emphasizes that strengthening the implementation of the code of ethics for PAUD teachers depends not only on regulation but also on moral awareness, ethical supervision in schools, and support through continuous professional development and adequate welfare. Therefore, the internalization of professional ethical values needs to be systematically integrated into educational policies and teacher development programs to cultivate educators who are competent, ethical, and dignified.